Que los muertos descansen en paz : el segundo caso del detective Cooper - Nunn, Malla (Nuevos tiempos (Madrid, Spain), 2012)
A stunning novel about murder, power, and a dangerous South African underworld. Cooper works undercover surveillance on the seedy Durban docks, but when a young boy is brutally murdered he must elude the police to conduct his own investigation. He discovers an international tussle for the political soul of South Africa.